2017
DOI: 10.1371/journal.pone.0172565
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a game? A systems approach to enhancing performance analysis in football

Abstract: PurposePerformance analysis (PA) in football is considered to be an integral component of understanding the requirements for optimal performance. Despite vast amounts of research in this area key gaps remain, including what comprises PA in football, and methods to minimise research-practitioner gaps. The aim of this study was to develop a model of the football match system in order to better describe and understand the components of football performance. Such a model could inform the design of new PA methods.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 48 publications
0
82
0
2
Order By: Relevance
“…For the analysis of offensive performance, recent studies have suggested that tactical performance measures should not be directly related to the probability of goal scoring, but other dimensions related to creating space and disordering the opposing defense should be considered when analyzing styles of play in soccer [24,25]. For that reason, in addition to goal and goal scoring opportunities, the analysis of successful penetration through defensive lines have been suggested as a novel dimension to study the offensive performance in recent studies [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis of offensive performance, recent studies have suggested that tactical performance measures should not be directly related to the probability of goal scoring, but other dimensions related to creating space and disordering the opposing defense should be considered when analyzing styles of play in soccer [24,25]. For that reason, in addition to goal and goal scoring opportunities, the analysis of successful penetration through defensive lines have been suggested as a novel dimension to study the offensive performance in recent studies [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of 'subjects matter experts' in the above research emphasises the need to incorporate the unique knowledge of experts into applied sports science research (McLean, Salmon, Gorman, Read, & Solomon, 2017). The Delphi method, is another method used to solicit knowledge from experts, and to collate and synthesise their opinions in order to create group consensus across multiple rounds of questionnaires (Hsu & Sandford, 2007;Mullen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, contributions to this special issue cover land use planning and urban design, construction, nanotechnologies, and robotics, and road and rail transport. Moreover, other recent applications of STST and related approaches in the wider Human Factors literature have been undertaken in areas such as sport (Mclean et al, ), freight transport (Murphy, Robertson, Huang, Jeffries, & Dainoff, ), regulatory system design (Carden, Goode, Read, & Salmon, ), sustainability (Siddiqi & Collins, ), and healthcare (Carayon, ). This is encouraging to see, and further applications in new areas are encouraged (M. C. Davis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps in response to increasing complexity levels and technology uptake in the core industries within which Human Factors is applied, recently there has been an explosion of STST within Human Factors research and practice. Notably, applications of STST and related approaches have begun to appear outside of work design, for example in the design of transport systems (e.g., Read., Beanland, Lenne, Stanton & Salmon, ; Salmon, Read, Walker, Lenne, & Stanton, ) and in the analysis of elite sport (e.g., Mclean, Soloman, Gorman & Salmon, ). The present special issue was proposed on the basis of this renewed interest in STST and systems thinking within Human Factors research and practice.…”
Section: Sociotechnical Systems Theorymentioning
confidence: 99%